The stoicheiometry of the sodium pump - Garrahan, P. J. (1967)
1. When resealed ghosts containing adenosine triphosphate (ATP), magnesium and sodium were incubated in a medium containing potassium, ATP was hydrolysed vigorously by a ouabain-sensitive mechanism. If the ghosts contained potassium instead of or in addition to sodium, and the external solution contained sodium but no potassium, there was little ouabain-sensitive hydrolysis of ATP. As it is known that the ouabain-sensitive ATPase in fragmented ghosts requires both sodium and potassium ions, these results show that the ATPase is activated by potassium externally and by sodium internally, and suggest that the ions activating the ATPase are the ions that are transported. 2. Resealed ghosts containing ATP, magnesium and sodium were incubated in sodium-free media containing potassium, with and without ouabain, and the rate of loss of sodium and rate of hydrolysis of ATP were measured. The hydrolysis of 1 molecule of ATP by the ouabain-sensitive mechanism was accompanied by the ouabain-sensitive loss of about 3 sodium ions. 3. (24)Na and (42)K were used to measure sodium efflux and potassium influx in identical batches of fresh red cells under the same conditions and at the same time. Each flux was measured in the presence and absence of ouabain. The ratio (ouabain-sensitive sodium efflux)/(ouabain-sensitive potassium influx) was significantly greater than 1 (1·20 ± 0·01 and 1·35 ± 0·01 in two experiments). If a small fraction of the potassium influx represented a ouabain-sensitive potassium: potassium exchange, the ratio of the numbers of ions moved in the sodium: potassium exchange catalysed by the pump must have been even further from unity. 4. Resealed ghosts containing [γ-(32)P]ATP, magnesium, (24)Na and orthophosphate were incubated in balanced salt solutions with and without potassium and with and without ouabain. A comparison of sodium efflux, estimated from (24)Na loss, with ATP hydrolysis, estimated from the formation of [(32)P]orthophosphate, showed that the sodium:sodium exchange in a potassium-free medium was accompanied by little or no ouabain-sensitive hydrolysis of ATP. 5. Experiments on intact red cells loaded with (24)Na showed that both sodium:sodium exchange in a potassium-free medium, and sodium:potassium exchange in a medium containing potassium, were partially inhibited by oligomycin (1-10 μg/ml.). Inhibition of the sodium:potassium exchange was not affected by raising the external potassium concentration.